CD137 promotes proliferation and survival of human B cells - Zhang, Xiaoyu (2010)
CD137 (4-1BB)-mediated costimulation plays an important role in directing the fate of Ag-stimulated T cells and NK cells, yet the role of CD137 in mediating B cell function is unknown. We found that CD137 is expressed in vitro on anti-Ig–stimulated peripheral blood B cells and in vivo on tonsillar B cells with an activated phenotype. In vitro CD137 expression is enhanced by CD40 stimulation and IFN-g and is inhibited by IL-4, -10, and -21. The expression of CD137 on activated human B cells is functionally relevant because engagement with its ligand at the time of activation stimulates B cell proliferation, enhances B cell survival, and induces secretion of TNF-a and -b. Our study suggests that CD137 costimulation may play a role in defining the fate of Agstimulated human B cells.